1997
DOI: 10.1074/jbc.272.13.8717
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Brain-specific Cationic Amino Acid Transporter

Abstract: rCAT3 (rat cationic amino acid transporter 3), a cDNA that encodes a novel member of the murine CAT family was isolated. The protein encoded by rCAT3 contained 619 amino acids, 53-58% of which were identical with those of the murine CAT family proteins previously described (mouse CAT1, CAT2a, CAT2b, and rat CAT1). Transient expression of rCAT3 and L-[14 C]arginine incorporation experiments in COS7 cells verified a high affinity system y ؉ transporter activity of rCAT3. First, rCAT3-mediated L-[ 14 C]arginine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 30 publications
2
61
1
1
Order By: Relevance
“…However, in our hands we were unable to entirely block the immunofluorescence signal by preincubation with the Cat3-immunizing peptide. Therefore the Cat3 antibody was used to probe for Cat3 expression in mouse brain where Cat3 expression has been described (12,16). Immunopositive regions of the normal adult mouse brain were in agreement with the in situ data previously reported (12) (data not shown).…”
Section: Cat3 Is Induced In Cat1supporting
confidence: 77%
See 3 more Smart Citations
“…However, in our hands we were unable to entirely block the immunofluorescence signal by preincubation with the Cat3-immunizing peptide. Therefore the Cat3 antibody was used to probe for Cat3 expression in mouse brain where Cat3 expression has been described (12,16). Immunopositive regions of the normal adult mouse brain were in agreement with the in situ data previously reported (12) (data not shown).…”
Section: Cat3 Is Induced In Cat1supporting
confidence: 77%
“…Ϫ/Ϫ cells is characteristic of Cat3 transport (12,16). These data indicate that both Cat1 ϩ/ϩ and Cat1 Ϫ/Ϫ MEF cells possess System y ϩ transport activity.…”
Section: System Ymentioning
confidence: 55%
See 2 more Smart Citations
“…Recent studies have identified cDNAs encoding two transmembrane proteins, CAT-1 and CAT-2(B), which have amino acid transport properties consistent with system y + [165,167]. A cDNA encoding rCAT3, a brain-specific protein which also exhibits system-y + activity, has recently been isolated from rats [169]. Still unresolved is the question of whether system y + consists solely of these proteins or involves other proteins as yet unidentified.…”
Section: Arginine Transportmentioning
confidence: 99%